(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Pornography today is a very common phenomenon that is seen to be prevalent across all the strata of individuals we come across. We as a society fail to recognize the impact of pornography on our community, as we are all always trying to ignore the problem concerning pornography. This article focuses on the various aspects of porn and its impact on our psychological, physical, and social life. It also brings us to notice that porn is not affecting aspects of our health but also gives rise to sexual violence and addictive behavior in us.